Dilated Cardiomyopathy Related to Hyperthyroidism in Young Adults - Sudarmika, Kadek Adi; Wulandari, Ni Luh Eka Sriayu (CoinReads Media Prima, 2024)
Introduction: DCM is characterised by myocardial structural and functional abnormalities not caused by ischemia. One cause is hyperthyroidism. Hyperthyroidism can lead to a hyperdynamic circulatory state, increasing cardiac output and metabolic demands, which can ultimately result in heart failure. Case: A 35-year-old woman presented with complaints of acute shortness of breath that worsened at night, accompanied by bilateral lower limb oedema and palpitations. Her medical history revealed hyperthyroidism diagnosed in 2021, but the patient was not compliant with treatment. Physical examination showed low blood pressure (84/60 mmHg), tachycardia 110 Beats Per Minute (BPM), and elevated Jugular Venous Pressure (JVP). Auscultation detected fine bilateral crackles and mitral regurgitation. Bilateral lower limb oedema. Echocardiography showed global hypokinesia with an Ejection Fraction (EF) of 30%, consistent with DCM. Laboratory tests revealed hyponatremia, elevated creatinine, and significantly increased liver enzymes. Initial management included intravenous saline infusion, continuous dobutamine infusion, and high-dose furosemide drip, which did not respond to furosemide. Acetazolamide was introduced as an additional diuretic. The patient also received ramipril, spironolactone, and enoxaparin for comprehensive cardiovascular and electrolyte imbalance management. This case highlights the importance of recognising the multifactorial nature of heart failure, particularly in patients with hyperthyroidism. Conclusion: This case illustrates the complexity of treating DCM with hyperthyroidism and the need for individualized therapy to optimize patient outcomes. The addition of acetazolamide proved effective in addressing the inadequate response to furosemide, emphasizing its role in enhancing diuretic response.